2019
DOI: 10.1002/celc.201901456
|View full text |Cite
|
Sign up to set email alerts
|

Water Splitting Performance Enhancement of the TiO2 Nanorod Array Electrode with Ultrathin Black Phosphorus Nanosheets

Abstract: Metal free two‐dimensional (2D) semiconductor nanomaterial black phosphorus (BP) is a promising photocatalyst for solar H2 evolution. Here, ultrathin BP nanosheets were prepared through organic salt sodium citrate assisted exfoliation of bulk BP. Further, an efficient photoelectrode for photoelectrochemical water splitting was developed based on TiO2 nanorod arrays, coated with ultrathin black phosphorus nanosheets. Compared to the pure TiO2 nanorod arrays, this structure exhibits reduced photoluminescent emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The Raman spectra showed three typical vibration modes of BPN, namely the out-ofplane vibration mode of A g 1 at 364 cm −1 , the in-plane vibration mode of B 2g at 442 cm −1 , and the in-plane vibration mode of A g 2 at 470 cm −1 . These results were consistent with the measurements made by Xu et al [33]. However, due to the much weaker peak of BPN compared to TDNA, it was difficult to display in the Raman spectra of BPN/TDNA.…”
Section: Structure and Morphology Of The As-synthesized Electrodessupporting
confidence: 93%
“…The Raman spectra showed three typical vibration modes of BPN, namely the out-ofplane vibration mode of A g 1 at 364 cm −1 , the in-plane vibration mode of B 2g at 442 cm −1 , and the in-plane vibration mode of A g 2 at 470 cm −1 . These results were consistent with the measurements made by Xu et al [33]. However, due to the much weaker peak of BPN compared to TDNA, it was difficult to display in the Raman spectra of BPN/TDNA.…”
Section: Structure and Morphology Of The As-synthesized Electrodessupporting
confidence: 93%
“…The authors claimed that the intrinsic p-type BP could boost hole extraction from BiVO 4 and thus extend holes’ trapping lifetime. Xu et al prepared a BP/TiO 2 heterostructure photoanode with longer carrier lifetime and stronger photocurrent density (increased by ∼140%) due to the efficient charge separation and transfer. Besides two-dimensional atomically thin BP nanosheets, zero-dimensional BP quantum dots (BPQDs) exhibit extra appealing properties such as size- and composition-dependent light absorption, remarkable quantum confinement and edge effects, long exciton lifetime, and modifiable surface, which play a vital role in the catalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Under light irradiation, TiO 2 nanorods coated with BP nanosheets show a 140% increase in the incidentphoto-current conversion efficiency (IPCE). 131 Similarly, enhancement of photocurrent densities of BP/Pt/RGO nano-akes electrode has been observed under >420 nm or >808 nm light irradiation when compared to dark. 121 Recently, it has been reported that van der Waals heterostructure of Pd dopped 1T-MoS 2 and BP nanosheet exhibits increased light absorption when compared to Pd-1T-MoS 2 .…”
Section: Photo-electrocatalysis (Pec)mentioning
confidence: 80%